Impact of the Malnutrition on Mortality in Patients With Osteoporosis: A Cohort Study From NHANES 2005-2010 - Shangguan, Xiaohui; Xiong, Jialing; Shi, Shanshan; Liao, Ying; Chen, Liling; Deng, Jiayi; Wu, Wanxia; Wang, Junjie; Tu, Jiabin; Xiu, Jiaming; Wu, Weihao; Chen, Longtian; et al. (Frontiers in Nutrition, 2022)
Background Osteoporosis is the most common metabolic bone disease. Recent studies have shown that malnutrition can promote the development of osteoporosis. However, the incidence of malnutrition in patients with osteoporosis and the relationship between malnutrition and all-cause mortality has not been adequately studied. Therefore, our study investigated the relationship between malnutrition and all-cause mortality in patients with osteoporosis. Methods We analyzed data on 7,700 adults ≥20 years of age during National Health and Nutrition Examination Survey (NHANES) 2005-2010. Each patient was assigned to one of three groups: normal nutritional status, mild malnutrition, and moderate to severe malnutrition. Survival curves and univariate and multivariable cox regressions based on the NHANES recommended weights were used to assess the association between malnutrition status and mortality. Moreover, cox proportional hazards regression analyses were performed on the matched pairs. Results Overall, 7,700 eligible individuals with osteoporosis were included in the final analysis, and the mean age was 52.0 ± 0.4 years. From the Kaplan–Meier curves for long-term all-cause mortality of malnutrition, worsening malnutrition status was associated with higher incidence of all-cause mortality. In the fully adjusted models, the adjusted hazard ratio (aHR) was 1.54 [95% confidence interval (CI), 1.02–2.31, p = 0.039] at mild malnutrition status and 2.70 (95%CI, 1.95–3.74, p < 0.001) at moderate to severe malnutrition status. The cox model after matching indicated that malnutrition was still a high mortality risk than no malnutrition (aHR = 2.23, 95% CI, 1.66–3.01, p < 0.001). Conclusions Poor malnutrition status, common in osteoporotic patients, is strongly associated with a risk for all-cause mortality comparable to that seen with normal nutritional status. These findings highlight the importance of risk stratification for nutritional status in osteoporotic patients and the implementation of strategies that is now available to help prevent malnutrition in these patients.